2020
DOI: 10.2166/wh.2020.082
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical and bacteriological quality of groundwater in a rural area of Western Niger: a case study of Bonkoukou

Abstract: The precariousness of the rural population in Africa is often symbolized by the lack of potable and safe drinking water. This study investigates the physico-chemical and bacteriological characteristics of 32 water samples with respect to WHO standards. The water samples were collected from wells, boreholes and small drinking water supply systems (DWS) in and around the township of Bonkoukou (Niger). The Water Quality Index (WQI) tool was used to assess the overall water quality with different physico-chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 10 publications
2
11
0
1
Order By: Relevance
“…− , Cu, Ni, Pb, and Zn concentrations that resulted from anthropogenic activities (agriculture, house holding, and industry) [23,64]. Some studies on groundwater from Asia (Bokaro district, India) and Africa (Bonkoukou, Niger) indicated high values for the WQI (>150), showing inadequacy for drinking purposes or poor quality, due to the anthropogenic activities (agricultural waste, untreated domestic waters), but also due to natural processes (rock weathering, intrusion of sea water) [65][66][67][68]. In Europe, studies on karstic waters in the Megara basin, Greece indicated generally good water quality (WQI < 100) with few cases of poor water quality [5].…”
Section: Water Quality Indicesmentioning
confidence: 99%
“…− , Cu, Ni, Pb, and Zn concentrations that resulted from anthropogenic activities (agriculture, house holding, and industry) [23,64]. Some studies on groundwater from Asia (Bokaro district, India) and Africa (Bonkoukou, Niger) indicated high values for the WQI (>150), showing inadequacy for drinking purposes or poor quality, due to the anthropogenic activities (agricultural waste, untreated domestic waters), but also due to natural processes (rock weathering, intrusion of sea water) [65][66][67][68]. In Europe, studies on karstic waters in the Megara basin, Greece indicated generally good water quality (WQI < 100) with few cases of poor water quality [5].…”
Section: Water Quality Indicesmentioning
confidence: 99%
“…nitrates and or chlorides [11,12,13,14]. Recent research have implicated on-site sanitation facilities such as pit latrines, leaking septic, waste water flowing on the surface and other improper waste disposal methods serving as point sources of groundwater contamination in many urban areas [15,16], peri urban [1] and rural areas [17,18] in SSA. In addition, faecal pollution of groundwater sources has been linked to infiltration of contaminated surface water [19].…”
Section: Introductionmentioning
confidence: 99%
“…They also find abnormal concentrations of NO 2 and NO 3 in almost half of analysed samples, which may have great danger for the population, especially for the juvenile population. 19 High nitrate concentrations are reported in some groundwater studies in Nigeria, Morocco and Togo. 20,21,22 The pH of drinking water has no immediate direct effects on human health but has some indirect health effects by bringing changes in other water quality parameters such as solubility of metals and survival of pathogens.…”
Section: Table 2 Selected Chemical-physical Parameters Their Median Values In All Water Wells and Comparison With The National Regulationmentioning
confidence: 97%